Introduction - Foreclosure Crisis in the United States: Families and Communities at Risk - Aguirre, Adalberto (Social justice, 2013)
An introduction is presented discussing the issue's articles which focus on the effects of the real estate foreclosure crisis on families and communities in the U.S.